Updated guidelines for the management of paracetamol poisoning in Australia and New Zealand. Issue 4 (1st December 2019) - Chiew, Angela L; Reith, David; Pomerleau, Adam; Wong, Anselm; Isoardi, Katherine Z; Soderstrom, Jessamine; Buckley, Nicholas A
Abstract: Introduction: Paracetamol is a common agent taken in deliberate self‐poisoning and in accidental overdose in adults and children. Paracetamol poisoning is the commonest cause of severe acute liver injury. Since the publication of the previous guidelines in 2015, several studies have changed practice. A working group of experts in the area, with representation from all Poisons Information Centres of Australia and New Zealand, were brought together to produce an updated evidence‐based guidance. Main recommendations (unchanged from previous guidelines): The optimal management of most patients with paracetamol overdose is usually straightforward. Patients who present early should be given activated charcoal. Patients at risk of hepatotoxicity should receive intravenous acetylcysteine. The paracetamol nomogram is used to assess the need for treatment in acute immediate release paracetamol ingestions with a known time of ingestion. Cases that require different management include modified release paracetamol overdoses, large or massive overdoses, accidental liquid ingestion in children, and repeated supratherapeutic ingestions. Major changes in management in the guidelines: The new guidelines recommend a two‐bag acetylcysteine infusion regimen (200 mg/kg over 4 h, then 100 mg/kg over 16 h). This has similar efficacy but significantly reduced adverse reactions compared with the previous three‐bag regimen. Massive paracetamol overdoses that result in high paracetamol concentrations more than double the nomogram line should be managed with an increased dose of acetylcysteine. All potentially toxic modified release paracetamol ingestions (≥ 10 g or ≥ 200 mg/kg, whichever is less) should receive a full course of acetylcysteine. Patients ingesting ≥ 30 g or ≥ 500 mg/kg should receive increased doses of acetylcysteine.